Design and fabricate real-time internet of things (IoT) monitoring system for floating solar photovoltaic (PV) system - Ting, Kai Zin (2023)

(untitled)
Due to increasing global need for renewable energy, photovoltaic systems have grown in popularity. Solar photovoltaic panel is one of the power generators that emits zero greenhouse gases in the process of energy conversion from sunlight to electricity. While there are different solar panel mounting methods, several studies show that floating type photovoltaic systems have improved energy conversion efficiency and power output. This is because conventional photovoltaic systems that are mounted on ground and roof-top can absorb a lot of heat from sunlight. The maximum power generated and efficiency of solar panels decrease as the temperature of the panels rises. Meanwhile, floating type photovoltaic system is one of the alternatives for limited land space for solar panel system installation. To evaluate and analyse the performance of floating type photovoltaic system, and compare the performance with ground mounted photovoltaic system, an IoT data monitoring system is designed and fabricated in this project. The purpose of using an IoT data monitoring system is to obtain real time data. In other words, to acquire the most recent information about the status of the solar panels immediately following data collection. The major function of the IoT data monitoring system includes gathering data from the solar panel and its surroundings, and sending it to a cloud server. In this project, Google Spreadsheet was configured as the cloud server using Google Apps Script. To obtain accurate data readings, the measurement system has been calibrated and validated. As a result, an IoT data collection and data monitoring system with percentage error around 1.5 % was developed and implemented.